Dietary Magnesium Intake Affects the Association Between Serum Vitamin D and Type 2 Diabetes: A Cross-Sectional Study - Weichao Huang (Frontiers Media S.A., 2021)
Introduction: Circulating vitamin D concentrations have been associated with the risk of type 2 diabetes (T2D). Magnesium has also been reported to be associated with lower T2D risk. Besides, magnesium is an essential cofactor for vitamin D activation. However, the effect of dietary magnesium intake on the association between vitamin D and the risk of T2D has not been studied comprehensively. Therefore, we designed this cross-sectional study to assess the effect modification of magnesium intake on the association between vitamin D and risk of T2D.Research Design and Methods: The present study analyzed data from the National Health and Nutrition Examination Survey (NHANES) continuously from 2007 to 2014, involving 10,249 participants. By having stratified participants based on magnesium intake category (low magnesium intake <267 mg/day; high magnesium intake: ≥267 mg/day), we further evaluated the difference (interaction test) between the relationship of vitamin D with the risk of T2D among low magnesium intake participants and high magnesium intake participants using weighted multivariable logistic regression.Results: In this cross-sectional study, the association of serum vitamin D with the incidence of T2D appeared to differ between the low magnesium intake group and the high magnesium intake group (OR: 0.968, 95%Cl: 0.919–1.02 vs. OR: 0.925, 95%Cl: 0.883–0.97). Furthermore, there was evidence of interaction between vitamin D levels and magnesium intake on decreasing the incidence of T2D (p-value for interaction = 0.001).Conclusions: The results of our study indicated that magnesium intake might affect the association of serum vitamin D with the risk of T2D. Such a finding requires further randomized controlled trials to provide more evidence.